Structural and functional studies of mutations affecting the UBA domain of SQSTM1 (p62) which cause Paget's disease of bone. (26th October 2004) - Layfield, R.; Ciani, B.; Ralston, S.H.; Hocking, L.J.; Sheppard, P.W.; Searle, M.S.; Cavey, J.R.
Abstract : Mutations affecting the UBA (ubiquitin-associated) domain of SQSTM1 (Sequestosome 1) (p62) are a common cause of Paget's disease of bone. The missense mutations resolve into those which retain [P392L (Pro 392 →Leu), G411S] or abolish (M404V, G425R) the ability of the isolated UBA domain to bind Lys-48-linked polyubiquitin. These effects can be rationalized with reference to the solution structure of the UBA domain, which we have determined by NMR spectroscopy. The UBA domain forms a characteristic compact three-helix bundle, with a hydrophobic patch equivalent to that previously implicated in ubiquitin binding by other UBA domains. None of the mutations affect overall folding of the UBA domain, but both M404V and G425R involve residues in the hydrophobic patch, whereas Pro-392 and Gly-411 are more remote. A simple model assuming the isolated UBA domain is functioning as a compact monomer can explain the effects of the mutations on polyubiquitin binding. The P392L and G411S mutations do however have subtle local effects on secondary structure, which may become more relevant in full-length SQSTM1. Identification of the in vivo ubiquitylated substrates of SQSTM1 will be most informative in determining the functional significance of the SQSTM1–ubiquitin interaction, and consequences of the disease-associated mutations.